Who is most affected by the Corona crisis? An analysis of changes in stress and well-being in Switzerland. (19th February 2021) - Kuhn, Ursina; Klaas, Hannah S.; Antal, Erika; Dasoki, Nora; Lebert, Florence; Lipps, Oliver; Monsch, Gian-Andrea; Refle, Jan-Erik; Ryser, Valérie-Anne; Tillmann, Robin; Voorpostel, Marieke
ABSTRACT: This study analyses the consequences of the Covid-19 crisis on stress and well-being in Switzerland. In particular, we assess whether vulnerable groups in terms of social isolation, increased workload and limited socioeconomic resources are affected more than others. Using longitudinal data from the Swiss Household Panel, including a specific Covid-19 study, we estimate change score models to predict changes in perceived stress and life satisfaction at the end of the semi-lockdown in comparison to before the crisis. We find no general change in life satisfaction and a small decrease in stress. Yet, in line with our expectations, more vulnerable groups in terms of social isolation (young adults, Covid-19 risk group members, individuals without a partner), workload (women) and socioeconomic resources (unemployed and those who experienced a deteriorating financial situation) reported a decrease in life satisfaction. Stress levels decreased most strongly among high earners, workers on short-time work and the highly educated.